The Conjoint Family Drawing: A Tool to Explore About Family Relationships - Gennari, Marialuisa; Tamanza, Giancarlo (Frontiers in Psychology, 2022)
In this article we will present a synthetic coding system of the Conjoint Family Drawing, a graphic-interactive tool developed to evaluate family relationships. A presentation of the analytical coding system is provided; such system consists of a grid, formed by two distinct levels of observation: the analysis of the product, which, in turn focuses on two levels, the global-familiar one (given by the overall drawing) and the individual one (given the individual members’ drawings), and the analysis of the drawing process (what happens during the realization of the drawing), which is made up of the observations of family interactions at the individual and group level. Consistently with our objectives and the theoretical literature on family drawing, 10 indicators for product analysis and 9 indicators for process analysis have been identified. A sample of 117 Conjoint Family Drawings was analyzed in order to verify the coding system’s applicability and effectiveness. The sample was constituted according to a convenience (not probabilistic) criterion. Following, a computing system was developed to allow the investigation of the overall family functioning through three steps: 1) the analysis of the frequency distribution of each indicator, in order to verify the non-determinability rates and the distribution of the different answer options; 2) a two-step cluster analysis, to determine homogeneous groups of Conjoint Family Drawings and identify, within each cluster (and comparatively between the clusters), the indicators and answer modalities that mostly affect the clusters’ aggregation itself; 3) the development of a synthetic system to code the Conjoint Family Drawing, beginning with the indicators that define the typological profiles of the clusters obtained. The synthetic system was developed through a summative and logical-combinatorial method, merging the most discriminating and clinically significant coding items, that is, those that are best associable to specific ways of family functioning. Seven family types emerged from these analyses: families characterized by optimal functioning, families characterized by adequate functioning, families characterized by chaotic functioning, families characterized by fragile paternity, families characterized by separate functioning, families with multiproblematic functioning and residual families. The characteristics of these family types will be outlined in this article.